Inhibition of protein synthesis in vitro by a lectin from Momordica charantia and by other haemagglutinins. - Barbieri, L (1979)
Protein synthesis by a rabbit reticulocyte lysate is inhibited by the haemagglutinating lectins from Momordica charantia and Crotalaria juncea seeds and from the roe of Rutilus rutilus, and by a commercial preparation of the mitogenic lectin from Phytolacca americana. The haemagglutinins from the seeds of Ricinus communis and of Vicia cracca acquired inhibitory activity after their reduction with 2-mercaptoethanol.